INFORMATION SYSTEM DEVELOPMENT PLAN FOR KIAN GENERAL MERCHANDISE - Krisha Claire H. Dionola; Arvine Jane B. Del Carmen; Jhon Lurym D. Delos Santos; Jean Michelle B. Catipay; Glendell R. Jadraque (International Journal of Innovations in Engineering Research and Technology, 2021)
One in close proximity is a store that sells reasonably priced items that many buyers use on a regular basis. Not just the average shopper, but even dealers. Sales, marketing, reports, capital management, customer support, supply, distribution, and other transactions were all part of the business processes that helped operate a business for years. Moreover, every aspect of reports and transactions, including those involving customers and supply was handled manually causing the company to run much slower and earn a much smaller profit when it came to sales. Many issues have arisen over the course of a business’s long history, such as a lack of consumers and stocks, maintenance, sales ranking, and inconsistency. A response would be the proposed Customer Relationship Management (CRM) framework and Supply Chain Management (SCM), which would provide reliability and better performance in business problems. These information systems aid companies in improving profitability by improving customer service, supply management that cause increasing efficiency. The importance of effective customer relationships as a key to customer value and hence shareholder value is widely emphasized. In order to enhance these relationships, the application of IT to marketing through customer relationship management (CRM) software, e-commerce and other initiatives is growing rapidly [1]. Modern Supply Chain Management (SCM) begins with the premise that supply chain participants are primarily interested in optimizing their own goals, and this self-serving emphasis typically results in inferior performance. Another way of thinking about this by considering a sequence of optimum regional policies does not yield a maximum response worldwide [2].